INOVASI DISRUPSI KEUANGAN SYARIAH DI ERA DIGITAL UNTUK MENDUKUNG KEBERLANJUTAN PEREKONOMIAN GLOBAL - Vida Maria Ulfa; Achmad Miftachul Huda (JURNAL INOVASI SAINS TEKNOLOGI DAN BISNIS, 2025)
In order to support global sustainability, the principles of Sharia finance in the digital era can be a driver for a fairer, more inclusive, and sustainable financial system. The application of these principles can help reduce economic imbalances, promote responsible business practices, and promote socially and environmentally sustainable financial development. Therefore, the main objective of writing this work is to analyze the results of technology that has brought innovation to Islamic financial services in improving accessibility, efficiency, and customer experience in the Islamic banking sector. Through this research, it was found that the principles of Islamic finance emphasize the avoidance of usury, which can prevent the exploitation of society and the environment, encourage fair and equitable risk sharing in financial transactions, and reduce social and economic inequality.